Morphological and topographic study of diaphyseal nutrient foramen of femur and its clinical implications in North Indian population - Jha, Shweta; Chauhan, Renu (International Journal of Research in Medical Sciences, 2017)
Background: Nutrient foramen of long bones defines the extent of bone vascularisation. Information regarding nutrient foramen is necessary to conserve circulation during orthopaedic and surgical procedures. The present study was conducted to examine the position, number and calibre of nutrient foramina in 100 dry femora belonging to North Indian population. Methods: The total length (TL) of each femur was measured by taking the measurement between the most proximal aspect of the head of the femur and the most distal aspect of the medial condyle. Number of nutrient foramina was determined by using a magnifying lens. Distance of nutrient foramen from upper end was measured. Direction and obliquity of nutrient foramina were noted. Position of nutrient foramina was determined in relation to length of femur and linea aspera. Caliber of nutrient foramen was measured using 18, 20, 22 and 24-gauge needles. Results: Length of femur on right side was 435.2 mm (Range 393-523 mm). Length of femur on left side was 437 mm (range 369-524). 78 (78%) femora had single nutrient foramen, 11 (11%) had double nutrient foramen and 11 (11%) had no nutrient foramen. All foramina were directed upwards. Maximum foramina were located in middle third of femur (84%) followed by upper third of femur (8%). Most common location was on the intermediate area between two lips of linea aspera (42%) followed closely by medial lip of linea aspera (36%). Conclusions: This study has provided additional data on the subject which will help in resection, surgical procedures and transplantation techniques by orthopedician in North Indian population.